Pemahaman Pendidikan Agama Islam dalam Membangun Lingkungan Religius Perspektif Orangtua - Reni Susilowati Latip; M. Dahlan R.,; Didin Hafidhuddin; Endin Mujahidin (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The religious environment was born from a family who understood the concept of Islamic Religious Education. The concept of Islamic Religious Education is formed according to human needs in life. The success of understanding Islamic Religious Education correctly will lead to the ability to manage and create a religious environment, a religious environment born from the family environment as the first place to explore abilities comfortably and safely. This study aims to determine the parents' understanding of Islamic religious education in shaping a religious environment. This research was conducted in 8 Hidayatullah Islamic Boarding Schools, carried out from January 5 to June 28, 2022. The method used was quantitative, with a sample of 223 people selected based on purposive sampling. Data retrieval is done by distributing a Google form questionnaire. The questions were developed in 7 items and validated through feed debriefing. Data were analyzed through basic percentages. The results showed that most parents understand Islamic Religious Education so as to create a religious environment. The implications of this research are expected to be a reference and consideration for parents, government and educational institutions in developing an understanding of Islamic Religious Education so as to form a family that is able to create religiosity in their lives.